Corporate in-house human capital investment in tax planning - CHEN, Xia (Institutional Knowledge at Singapore Management University, 2018)
In-house human capital tax investment is a significant input to a firm’s tax decisions. Yet,due to the lack of data, there is little empirical evidence on how corporate in-house taxdepartments are associated with tax planning and compliance outcomes. Using handcollected data on corporate tax employees in S&P1500 firms over the period 2009-2014, wefind that in-house tax planning investments lead to greater tax avoidance, in-house taxcompliance investments lead to lower tax risk, while general tax investments achieve bothgoals. We obtain the same inferences when controlling for endogeneity or using changespecifications. We also find that the effects of in-house tax investments are stronger for firmswithout auditor-provided tax services, for firms that have under-performed their industrypeers in tax planning and compliance in the past, and for tax employees with priorexperiences in big N and law firms. Overall, this paper contributes to the literature by lookinginside the “black box” of corporate tax departments.